2021
DOI: 10.1111/pce.14236
|View full text |Cite
|
Sign up to set email alerts
|

Global identification of full‐length cassava lncRNAs unveils the role of cold‐responsive intergenic lncRNA 1 in cold stress response

Abstract: Long noncoding RNAs (lncRNAs) have been considered to be important regulators of gene expression in a range of biological processes in plants. A large number of lncRNAs have been identified in plants. However, most of their biological functions still remain to be determined. Here, we identified a total of 3004 lncRNAs in cassava under normal or cold‐treated conditions from Iso‐seq data. We further characterized a cold‐responsive intergenic lncRNA 1 (CRIR1) as a novel positive regulator of the plant response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 64 publications
(74 reference statements)
0
25
1
Order By: Relevance
“…Researchers have extensively documented low-temperature stress-induced morphological changes in plants, and morphological changes are the most visible symptom of stress [28,29]. The plant height, tillers number and area of green leaves decreases significantly or even withers after low-temperature stress [9,30].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have extensively documented low-temperature stress-induced morphological changes in plants, and morphological changes are the most visible symptom of stress [28,29]. The plant height, tillers number and area of green leaves decreases significantly or even withers after low-temperature stress [9,30].…”
Section: Discussionmentioning
confidence: 99%
“…Also in Arabidopsis , lncRNA SVALKA can regulate cold tolerance in Arabidopsis [ 101 ] ( Figure 5 e). In cassava (Manihot esculenta Crantz) , CRIR1 (a cold-responsive intergenic lncRNA 1) is a positive regulator of the plant response to cold stress [ 136 ]. CRIR1 is significantly induced by cold treatment to interact with MeCSP5 (cassava cold shock protein 5) [ 136 ].…”
Section: Lncrnas Respond To Biotic and Abiotic Stressesmentioning
confidence: 99%
“…In cassava (Manihot esculenta Crantz) , CRIR1 (a cold-responsive intergenic lncRNA 1) is a positive regulator of the plant response to cold stress [ 136 ]. CRIR1 is significantly induced by cold treatment to interact with MeCSP5 (cassava cold shock protein 5) [ 136 ]. Further studies have found that CRIR1 may recruit MeCSP5 to improve the translation efficiency of mRNA.…”
Section: Lncrnas Respond To Biotic and Abiotic Stressesmentioning
confidence: 99%
See 2 more Smart Citations